A Study on Consumers' Online Stores Preferences: Comparison between Shopee and Lazada in Malaysia - Lok, Yee Huei; Madan, Sahana; Fatini, Nur Lidiya; Nayley, Nur; Adira, Nur Maizatul; Izzah, Nur; Ramachandra, Rashmi (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2022)
Nowadays, online stores are widespread all over the world. It is a website or an application where people can easily purchase goods and services over the internet. Online stores are known to be active in growing their businesses, especially since the Covid-19 outbreak, which urges people to think that online shopping is more convenient and safer than visiting the physical stores to buy their needs and wants. This research paper attempts to study the factors influencing the consumers’ online store preferences between Shopee and Lazada. The research was conducted through the distribution of a questionnaire to collect data on the consumers’ online store preferences. A total of 100 respondents have answered the questionnaire survey. The results indicate that factors including customer satisfaction, information quality, and performance expectancy can influence the consumers’ online stores preferences as well as impact the businesses of Shopee and Lazada. The findings also provide some feedback to assist these two organizations for better future business performance. Keywords: Consumer, COVID-19, Lazada, Malaysia, Online Stores, Preferences, Shopee